Effects of global postural re-education on stress and sleep quality in health sciences female students: a randomized controlled trial pilot study - Rodríguez-Aragón, Manuel; Varillas-Delgado, David; Gordo-Herrera, Javier; Fernández-Ezequiel, Alba; Moreno-Heredero, Berta; Valle, Noelia (Frontiers in Psychiatry, 2024)
Objective The purpose of this study was to determine, for the first time, whether the application of a self-management program with global postural re-education (GPR) influences stress and sleep quality in female health science students. Methods In this randomized controlled trial pilot study, forty-one female health science students were randomized into a control group (n=21) and an intervention group (n=20). Participants underwent 8 weeks of self-management with and without GPR, after familiarization and therapy training. Outcomes included the State-Trait Anxiety Inventory (STAI) questionnaire and cortisol levels in saliva measured with the “CORTISOL Saliva ELISA SA E-6000” kit. Sleep quality was measured with the Pittsburgh Sleep Quality Index (PSQI) and a Sleep Diary; total sleep time (TST), sleep onset latency (SOL), wakefulness after sleep onset (WASO), sleep efficiency (SE), and perceived sleep quality or satisfaction were assessed using the Likert scale. Results After self-treatment with GPR, participants in the intervention group showed lower cortisol levels compared to the control group (p = 0.041). Additionally, the intervention group demonstrated statistically significant improvements in sleep quality according to their PSQI (p = 0.010), STAI (p = 0.043), SOL (p = 0.049), and SE (p = 0.002). Conclusion This study shows that self-management through GPR helps reduce stress and improve sleep quality in female health science students. Clinical Trial Registration https://clinicaltrials.gov/, identifier NCT05488015.